Use of continuous positive airway pressure and non‐invasive ventilation for respiratory failure in an Australian aeromedical retrieval service: A retrospective case series. (14th April 2021) - Weller, Martin; Gibbs, Clinton; Pellatt, Richard; MacKillop, Allan
Abstract: Objective: The purpose of the present study was to investigate the use of respiratory support via continuous positive airway pressure (CPAP) and non‐invasive ventilation (NIV) in a medical retrieval service in Queensland, Australia, with reference to transport considerations and patient safety. Methods: In this unblinded retrospective case series over a 13‐month period, a clinical database was reviewed for the use of CPAP/NIV. Retrieval metrics as well as clinical data were recorded. Results: A total of 128 patients were transferred either by rotary (80%) or fixed wing (20%). The median transport time was 65 min. The median total mission time was 3.7 h. Fifty‐two percent of patients were female. The median age was 69 years and 93% had a background of cardiorespiratory disease. Sixty‐five percent of patients were receiving CPAP/NIV before arrival of the retrieval team. The main diagnoses were respiratory failure (29.7%), acute pulmonary oedema (26.6%) and chronic obstructive pulmonary disease (25.8%). There were no incidences of pneumothorax, intubation in transit, vomiting, desaturation, hypotension, cardiac arrest or death. In two cases NIV was abandoned due to mask intolerance and in one case there was a decrease in Glasgow Coma Scale by 2. In no cases was there a detrimental outcome for the patient. Conclusion: The use of NIV and CPAP appears to have a low‐risk profile in aeromedical retrieval even for prolonged periods of time in an adult population. Abstract : The use of CPAP and NIV in respiratory failure appears to have a low complication rate even for prolonged mission times in aeromedical retrieval.